2015
DOI: 10.1007/s00464-015-4620-0
|View full text |Cite
|
Sign up to set email alerts
|

Knotless choledochorraphy with barbed suture, safe and feasible

Abstract: The use of unidirectional knotless barbed suture (V-Loc 90) is safe, feasible and effective on LCBDE for primary common bile duct closure. The biliary leak rate is acceptably low and comparable to the rate reported in the literature. This report is our initial experience that needs further clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 26 publications
(23 reference statements)
0
17
1
Order By: Relevance
“…Edil et al [32] used barbed sutures in the performance of a pancreaticojejunostomy in the last 19 patients in a series of 37 undergoing Whipple procedure and concluded that the use of barbed sutures in performing laparoscopic pancreaticojejunostomy is a safe and effective technique, showing similar results to other series of laparoscopic Whipple procedures. Fernández et al [33] used barbed sutures in choledochorrhaphy in 50 patients. There were no bile leaks or other postoperative complications such as infection, need for reintervention, or death.…”
Section: Use Of Barbed Sutures In Bariatric Surgerymentioning
confidence: 99%
“…Edil et al [32] used barbed sutures in the performance of a pancreaticojejunostomy in the last 19 patients in a series of 37 undergoing Whipple procedure and concluded that the use of barbed sutures in performing laparoscopic pancreaticojejunostomy is a safe and effective technique, showing similar results to other series of laparoscopic Whipple procedures. Fernández et al [33] used barbed sutures in choledochorrhaphy in 50 patients. There were no bile leaks or other postoperative complications such as infection, need for reintervention, or death.…”
Section: Use Of Barbed Sutures In Bariatric Surgerymentioning
confidence: 99%
“…Lee and Yoon 26 performed primary closure of the CBD in 15 patients during choledochotomy and observed no biliary leakage in any patients; however, these patients required another endoscopic procedure to remove the endobiliary stent 1 month after surgery. In Mexico, Fernandaz et al 27 also proved that the use of unidirectional knotless barbed suture was safe and feasible in LCBDE for primary CBD closure. In our study, mild biliary leakage was observed in only one patient in each group, and they recovered with no further complications after conservative treatments.…”
Section: Discussionmentioning
confidence: 99%
“…V-Loc device consists of a helical barbed absorbable thread having a unidirectional barb with circumferential distribution having a loop at the end with a self-anchoring nature so that it does not loosen after initial tightening. 8,11,15,[20][21][22] These characteristics of V-Loc device eliminate the need for tying a knot and reinforcement for preventing thread slippage. V-Loc maintains even tensile strength along the total length of the wound without knot tying.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] Recently, knotless barbed absorbable sutures have been used in various surgical situations, including gastrointestinal surgery, [7][8][9][10] gynecologic surgery, [11][12][13] and hepatobiliary-pancreatic surgery. [14][15][16] Currently, V-Loc (Covidien, Mansfield, MA, USA), an absorbable wound closure device that is US Food and Drug Administration (FDA)-approved barbed suture, is a unidirectional barbed suture with a needle at one end and a welded loop at the other end. 17 We applied V-Loc TM 90 2-0 for abdominal wall closure after SILA.…”
Section: Introductionmentioning
confidence: 99%